A Study on Production and Marketing of Poultry Eggs in Tamilnadu - India (With Reference to Namakkal District) - Chandrakumarmangalam , S.; Vetrivel, S.C. (International Journal of Poultry Science, 2012)
The Indian poultry industry’s success story is uniquely exceptional. From a backyard venture, it has made a quantum leap to emerge as a dynamic industry. Over the last three decades, there have been significant developments in the poultry industry with each decade focusing on different sectors. The seventies saw a spurt in egg production; the eighties an acceleration in broiler production; the nineties advances in poultry integration, automation and feed production. The present decade promises to exploit value added products and the global trade avenue. India is a developing country primarily has an agricultural economy. If agriculture blooms, the country prospers. Agriculture is a diversified subject covers such activities as farming, forestry, animal husbandry and fishery including agro-based industries in broader concept. Rural development improves the quality life of the weaker sections and gives way for participation and involvement of the masses in the process of decision making in economic and social life of society. They provide livelihood to and million of rural house holds in the sub marginal level both land less and small landholders. They prove to be the best way to alleviate rural poverty and reduce income disparities. Industrial sector depends on agriculture for their raw material and allied products. Poultry and egg are popular food articles of high nutritional value and so and major break through have been achieved in egg production and broiler stock. This due to integrated development of breeding feeding, marketing, health care and nutrition etc. Poultry farming by providing additional income to the agricultures helps them to earn more and helps the nation to develop without any wide disparities in the income.